2018
DOI: 10.1029/2018gl079313
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Determination of Eutectic Liquid Compositions in the MgO‐SiO2System to the Lowermost Mantle Pressures

Abstract: We have performed melting experiments on the MgO-SiO 2 binary system to 139 GPa in a diamond anvil cell. Both MgO-MgSiO 3 and MgSiO 3 -SiO 2 eutectic compositions were examined by textural/chemical characterizations of recovered samples. Results demonstrate that the MgO-MgSiO 3 eutectic becomes more enriched in MgO with increasing pressure and is close in composition to Mg 2 SiO 4 at the core-mantle boundary (CMB) pressure. On the other hand, the MgSiO 3 -SiO 2 eutectic is more SiO 2 -rich at higher pressure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 37 publications
6
15
0
Order By: Relevance
“…The XSi value of the eutectic composition increases from 0.556 to 0.61 in a range from 1 to 13.5 GPa (down to ~400 km depth in the mantle) (Dalton and Presnall, 1997;Hudon et al, 2005; this study), which are close to those of Echondrites (0.533-0.577; Wasson and Kallemeyn, 1988). Using a DAC, experimentally determined eutectic compositions (XSi) at 41, 128, and 139 GPa were 0.60, 0.66, and 0.66, respectively (Ozawa et al, 2018). Combined with all the available experimentally determined eutectic compositions, the XSi increases significantly to ~0.61 with increased pressure when lower than 50 GPa and then increases asymptotically to 0.66 up to 128 GPa (Fig.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The XSi value of the eutectic composition increases from 0.556 to 0.61 in a range from 1 to 13.5 GPa (down to ~400 km depth in the mantle) (Dalton and Presnall, 1997;Hudon et al, 2005; this study), which are close to those of Echondrites (0.533-0.577; Wasson and Kallemeyn, 1988). Using a DAC, experimentally determined eutectic compositions (XSi) at 41, 128, and 139 GPa were 0.60, 0.66, and 0.66, respectively (Ozawa et al, 2018). Combined with all the available experimentally determined eutectic compositions, the XSi increases significantly to ~0.61 with increased pressure when lower than 50 GPa and then increases asymptotically to 0.66 up to 128 GPa (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…Nevertheless, there have been limited studies on the melting behavior of the MgSiO3-SiO2 system at high pressures: e.g., at 1 GPa using the piston cylinder (Hudon et al, 2005) and at 5 GPa using the Kawai-type multianvil apparatus (KMAA) (Dalton and Presnall, 1997). On the other hand, using a diamond anvil cell (DAC), melting experiments in the MgO-SiO2 system were carried out up to 139 GPa (Baron et al, 2017;Ozawa et al, 2018). According to these studies, the MgSiO3-SiO2 system displays eutectic melting and the XSi of the eutectic compositions systematically increases with increased pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The Eu-MFS sample is important for the accurate determination of solidus temperature, because an ideal eutectic composition would undergo complete melting without a mixed phase region of solid and liquid, providing maximum contrast in scattering properties across the melting point (Baron et al, 2017). We note that the existing studies are not in complete agreement on the eutectic composition at the lower-mantle conditions (de Koker et al, 2013;Ozawa et al, 2018). Even if the exact eutectic composition is not clearly known, the larger amount of melt generated from a near-eutectic composition would still improve the accuracy of melt detection because of the expected large production of melt at the solidus.…”
Section: Resultsmentioning
confidence: 88%
“…The chondritic composition in Andrault et al (2011) had a 0.44 mole fraction of SiO 2 , X (SiO 2 ), substantially higher than that of pyrolite (0.33). Both theoretical and experimental studies (de Koker et al, 2013; Ozawa et al, 2018) have shown that the eutectic X (SiO 2 ) value decreases from 0.4–0.42 to 0.3–0.38 with an increase in pressure from 25 to 136 GPa. Therefore, while the X (SiO 2 ) value of the chondritic composition is close to that of the eutectic composition at low pressures, the difference from eutectic composition would increase with pressure due to the decrease in eutectic X (SiO 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…(2017) (Ba17, brown), Ozawa et al. (2018) (O18, green) and Ohnishi et al. (2017) (O17, purple) are included, with triangles in the latter two bracketing the eutectic composition, along with results by Belmonte et al.…”
Section: Thermodynamic Descriptionmentioning
confidence: 99%